Peptide nucleic acid probe-assisted paper-based electrochemical biosensor for multiplexed detection of respiratory viruses - Lomae, Atchara; Teekayupak, Kanyapat; Preechakasedkit, Pattarachaya; Pasomsub, Ekawat; Ozer, Tugba; Henry, Charles S.; Citterio, Daniel; Vilaivan, Tirayut; Chailapakul, Orawon; Ruecha, Nipapan (ELSEVIER, 2024)
The similar transmission patterns and early symptoms of respiratory viral infections, particularly severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza (H1N1), and respiratory syncytial virus (RSV), pose substantial challenges in the diagnosis, therapeutic management, and handling of these infectious diseases. Multiplexed point-of-care testing for detection is urgently needed for prompt and efficient disease management. Here, we introduce an electrochemical paper-based analytical device (ePAD) platform for multiplexed and labelfree detection of SARS-CoV-2, H1N1, and RSV infection using immobilized pyrrolidinyl peptide nucleic acid probes. Hybridization between the probes and viral nucleic acid targets causes changes in the electrochemical response. The resulting sensor offers high sensitivity and low detection limits of 0.12, 0.35, and 0.36 pM for SARS-CoV-2 (N gene), H1N1, and RSV, respectively, without showing any cross-reactivities. The amplificationfree detection of extracted RNA from 42 nasopharyngeal swab samples was successfully demonstrated and validated against reverse-transcription polymerase chain reaction (range of cycle threshold values: 17.43-25.89). The proposed platform showed excellent clinical sensitivity (100%) and specificity (>= 97 %) to achieve excellent agreement (kappa >= 0.914) with the standard assay, thereby demonstrating its applicability for the screening and diagnosis of these respiratory diseases.
Keywords: Electrochemical detection; Amperometry; Label-free detection; Multiplexed detection; Paper-based analytical device; Swab samples; PYRROLIDINYL PNA; GUANINE; ADENINE; ASSAY; Chemistry